(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In this article, opinions are expressed about the theoretical basis of the development of regional tourism and its services market, as well as the factors that need to be paid attention to in its formation. Also, in the process of researching regional tourism, special attention is paid to studying the elements that make up the activity as a whole complex. In other words, among the main principles of the development and organization of domestic tourism, the principle of an integrated approach was emphasized.